Hypersalinity Drives Dramatic Shifts in the Invertebrate Fauna of Estuaries - Ben J. Roots; Ruth Lim; Stephanie A. Fourie; Essie M. Rodgers; Emily J. Stout; Sorcha Cronin-O’Reilly; James R. Tweedley (Animals)
In some estuaries, low inflow and/or isolation from the ocean can result in evapoconcentration and hypersalinity (≥40 ppt). This can create osmoregulatory and energetic challenges for the faunal community, leading to reductions in diversity as more species pass their thresholds. As climate change is increasing the magnitude and duration of hypersaline conditions, we used benthic macroinvertebrate data from 12 estuaries across a Mediterranean climatic region (southwestern Australia) to assess the influence of salinity (0–122 ppt) on the invertebrate fauna. Taxa richness and diversity were highest in salinities between 0 and 39 ppt, peaking at salinities closest to seawater, while total density peaked at 40–49 ppt. Beyond 50 ppt, these measures declined significantly. Community composition changed markedly along the salinity gradient. In lower salinities, communities were diverse, comprising polychaetes, malacostracans, hexapods, ostracods, bivalves, and gastropods. However, in salinities ≥50 ppt, many taxa declined, leading to communities dominated by polychaetes (mainly Capitella spp.) and hexapods (mostly larval chironomids). At 90 ppt, only polychaetes and hexapods remained, and at ≥110 ppt, only the latter taxon persisted. This faunal shift towards insect dominance in hypersaline conditions mirrors observations in other Mediterranean and arid/semi-arid regions, with the resulting communities resembling saline wetlands or salt lakes. This loss of invertebrates can substantially impact ecosystem functioning and trophic pathways, and the findings of this study provide a basis for predicting how these communities will respond to increasing hypersalinity driven by climate change.